The Influence of Leadership, Organizational Culture, And Training on Teacher Performance of The Al Ishlah Gorontalo Foundation Mediated by Employee Engagement - Jois Akase; Deni Gustiawan; Asep Saifudin; Mulyadi Mulyadi (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of leadership, organizational culture, and training on teacher performance at the Al Ishlah Gorontalo Foundation, with employee engagement as a mediating variable. Using a quantitative approach with 136 teachers selected through saturated sampling, data was analyzed using Structural Equation Modeling (SEM) with LISREL software. The findings revealed that organizational culture and training significantly influenced employee engagement, while leadership had no significant effect. Organizational culture directly impacted teacher performance, while training did not significantly affect performance. Employee engagement was proven to significantly affect teacher performance, but leadership, organizational culture, and training did not significantly influence performance through employee engagement as a mediator. The implications of these results suggest that fostering a positive organizational culture is crucial for improving teacher engagement and performance. Training programs should be more tailored to teachers’ needs to effectively enhance their performance, while leadership approaches should be reassessed to ensure they align with teachers' motivations. Furthermore, future studies could explore other factors, such as intrinsic motivation and peer support, to better understand their roles in enhancing teacher performance in educational settings.